Fear of the Dark? – How Access to Electric Lighting Affects Security Attitudes and Nighttime Activities in Rural Senegal - Gunther Bensch; Jörg Peters; Maximiliane Sievert (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
Providing access to electricity is widely considered as a precondition for socio-economic development in rural areas of developing countries. While electrification interventions are often expected to reduce poverty through productive uses for income generating purposes, the reality in rural usage patterns looks different: Electricity is often used for lighting and entertainment devices only. It is particularly lighting with its implications for security and convenience that explains the high importance beneficiaries assign to electrification. Against this background, this paper probes into the effects of Solar Home System electricity usage on lighting consumption and activities after nightfall using cross-sectional household-level data from rural Senegal. We apply a new matching algorithm to control for a possible self-selection into Solar Home System ownership and find substantially higher lighting usage and study time after nightfall of school children. We also find some indication for improvements in perceived security.
Keywords: O12; O13; O18; O22; 330; rural electrification; energy access; impact evaluation; matching